PENGELOLAAN EKOWISATA AIR TERJUN SEGENTER BERBASIS MASYARAKAT DI DUSUN KUMBI DESA PAKUAN LOMBOK BARAT - Jaelani, Muhammad; Anwar, Hairil; Wahyuningsih, Endah (JURNAL RIMBA LESTARI, 2023)
The tourism potential in Kumbi Hamlet, Pakuan Village, precisely in the Nuraksa Forest Park area, is very large. Ecotourism managers of Nuraksa Forest Park should make decisions and make ecotourism management strategies to attract local and foreign tourists. In fact, in the field, managers are still considered lacking in terms of managing the pattern of management of ecotourism potential in Kumbi hamlet and determining priority strategies to be developed. This study aims to determine the pattern of community-based ecotourism management and the prioritization of alternative pattern components that will be used in the management of segenter waterfall ecotourism. This type of research is qualitative and quantitative descriptive research using field study and interview approaches. The location of this research is in Kumbi Hamlet, with data sources from local communities and resource persons who are experts in the field of tourism, namely: kasi planning, and kasi tourism development. The data collection technique uses interviews and questionnaires. This research data analysis uses qualitative descriptive analysis techniques and Analytical Hierarchy Process (AHP) with the help of Expert Choice 11 software. The results showed that the existing patterns in the management of community-based ecotourism are patterns of education and environmental awareness, local capacity building, partnerships with external parties, and local economic empowerment. And the results for the highest criterion are planning by 35% and with alternative management strategy priorities, namely on the pattern of local economic empowerment with a value weight of 16.2%.